2019
DOI: 10.36456/jet.v4.n1.2019.1880
|View full text |Cite
|
Sign up to set email alerts
|

Needs Analysis on the Improvement of English for Informatics Courses Based on the Perception of Non-English Teachers of State Polytechnic of Malang

Abstract: The purpose of the present study was to reveal the needs analysis commissioned by the Information Technology Department regarding the non-English teachers' perceptions on the teaching and learning practices of the English language in the department. The study employed an online questionnaire and interview to 23 IT teachers. The questionnaire covered the five categories, namely English Language Teaching at IT Department, Language Skills and Components, Teaching Learning Activities, Teaching Skills, IT related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Categorizing the needs to three categories which are general needs, academic needs, and job needs, the study found that the competence expected are listening to the radio, doing the presentation in front of the class, and writing a CV. Focusing on teacher need, Asri, Ulfa, and Suryadi (2019), conducted a need analysis on the improvement of English for Informatics department. The study concluded that there should be improvement on the course syllabus, classroom activities and materials, as well as the evaluation process.…”
Section: Pjeementioning
confidence: 99%
“…Categorizing the needs to three categories which are general needs, academic needs, and job needs, the study found that the competence expected are listening to the radio, doing the presentation in front of the class, and writing a CV. Focusing on teacher need, Asri, Ulfa, and Suryadi (2019), conducted a need analysis on the improvement of English for Informatics department. The study concluded that there should be improvement on the course syllabus, classroom activities and materials, as well as the evaluation process.…”
Section: Pjeementioning
confidence: 99%
“…The first step was needs analysis which was conducted to find solutions to existing problems. Need analysis promotes outlining the learner's specific needs to achieve the desired outcomes (Asri et al, 2019). The needs analysis was done by observing and interviewing lecturers and students in the Electrical Engineering Study Program.…”
Section: Figure 1 Teaching Module Development Designmentioning
confidence: 99%